Factors Affecting Cyclist Behaviours in the Special Region of Yogyakarta - Danang Febrianto; Dewanti; Imam Muthohar (Journal of the Civil Engineering Forum, 2021)
Bicycle-riding/cycling has reportedly become a new trend in various cities of Indonesia, as well as the Special Region of Yogyakarta, amidst the social restriction applied by the Government to decrease the spreading rate of the COVID-19 virus. This is observed to be a healthier effort in strengthening the immune system during the pandemic. However, the positive growth of this trend is proportional to the increasing data on bicycle accidents. This was due to the increased rate of injured and dead victims from 2017 to 2020. The human behavior factor is also one of the factors causing the high rate of these bicycle accidents. Therefore, this study aims to analyze the factors affecting the behavior of cyclists in the Special Region of Yogyakarta, to reduce the continuous increase of accidents. The data used in this study were the result of the Cyclist Behavior Questionnaire (CBQ) on the Yogyakarta riders. The samples were obtained through the purposive sampling method, using an online questionnaire with a google form and acquiring 362 respondents. Furthermore, the analytical method used was the structural equation modeling (SEM), through the AMOS 22.0 software. The results indicated that the regulation scale directly affected risk perception and cyclist behaviors (risky and positive). However, age only affected their behaviors, which did not directly affect the accidents. The regulation scale then directly affected the risky behavior of cyclists, with risk perception observed as the mediator, implying that the cyclists' knowledge of road safety regulations influenced individual behaviors. In conclusion, these results are expected to be one of the considerations in the policy of the government, to carry out the overall development of transportation, especially bicycles.